2019
DOI: 10.12965/jer.1938624.312
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of injury incidences in the Korea national men’s soccer teams

Abstract: The purpose of this study was to identify the frequency and characteristics of injuries that occurred during the training camps and matches of the national soccer teams (under-20 [U-20], under-23 [U-23], A men's national teams). The research data were based on injuries that occurred from January 2016 to December 2017. The athletic trainer, a member of the Korea Football Association, recorded injuries based on the recording sheet of the Asian Football Confederation Daily Medical Report. A total of 1,689 (984 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Forwards were the most affected, similar to previous studies, ( 1 )-( 4 but in other studies midfielders were the most affected. ( 15 )-( 17 One hypothesis for this difference is that these studies did not subdivide midfielders into defensive (holding or anchor) and attacking midfielders.…”
Section: Discussionmentioning
confidence: 99%
“…Forwards were the most affected, similar to previous studies, ( 1 )-( 4 but in other studies midfielders were the most affected. ( 15 )-( 17 One hypothesis for this difference is that these studies did not subdivide midfielders into defensive (holding or anchor) and attacking midfielders.…”
Section: Discussionmentioning
confidence: 99%
“…The injuries were recorded by the medical staff using the Daily Medical Report provided by the Asian Football Confederation ( Hwang-Bo and Joo, 2019 ). The characteristics of the injuries (type of injury, location of injury, location of injury by playing position, and diagnosis of injury) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of the author’s knowledge, there are few studies that demonstrate the characteristics of injuries in highest-level soccer players, such as national team players. A previous study on the characteristics of injuries in the Korean male national team demonstrated that 85% of injuries occurred in lower extremities, and the most frequent types of injuries were contusions, muscle rigidity, and sprains ( Hwang-Bo and Joo, 2019 ). Most of the previous studies on the characteristics of injuries focus on high-level male soccer players ( Dauty and Collon, 2011 ; Ekstrand et al, 2011 ; Pfirrmann et al, 2016 ), and there are no studies on the characteristics of injuries in female players, especially national team soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Football is the most popular sport in the world, has the largest number of participants, and is associated with a high risk of injury at the professional, amateur, and youth levels during practices and matches [1][2][3][4][5]. It is estimated that somewhere between 13 and 35 players get injured every 1000 competitive hours.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that somewhere between 13 and 35 players get injured every 1000 competitive hours. The most common incidence of injuries occurs in the lower limbs, mostly ankle sprains [1,5,6]. Dvorak et al studied injury incidences in the 2010 International Federation of Association Football World Cup.…”
Section: Introductionmentioning
confidence: 99%